Marital Status and Return to Work After Living Kidney Donation. (September 2018) - Frech, Adrianne; Natale, Ginny; Hayes, Don; Tumin, Dmitry
Purpose: Living kidney donation is safe and effective, but patients in need of a transplant continue to outnumber donors. Disincentives to living donation include lost income, risk of job loss, perioperative complications, and unreimbursed medical expenses. Methods: This study uses US registry and follow-up data on living kidney donors from 2013 to 2015 to identify social predictors of return to work across gender following living kidney donation. Results: Using logistic regression, we find that predictors of return to work following living kidney donation differ for women and men. Among women, age, education, smoking status, and procedure type are associated with return to work. Among men, education, procedure type, and hospital readmission within 6 weeks postdonation are associated with return to work. Notably, single and divorced men are less likely to return to work compared to married men (odds ratio [OR] for single men 0.51, 95% confidence interval [CI], 0.37-0.69, P < .001; OR for divorced men 0.51, 95% CI, 0.34-0.75, P = .006). Marital status is not associated with return to work for women. Single and divorced men's greater odds of not returning to work are robust to controls for relevant pre- and postdonation characteristics. Conclusions: Single and divorced men's lack of social support may present an obstacle to work resumption following living kidney donation.